Lepidoptera pests collected in Eucalyptus urophylla (Myrtaceae) plantations during five years in Três Marias, State of Minas Gerais, Brazil - M Pereira, José M (2001)
Lepidoptera pest species from eucalyptus were collected in Eucalyptus urophylla plantations in the region of Três Marias, State of Minas Gerais, Brazil, every 15 days from June 1989 to June 1994 with five light traps. Twelve primary and 15 secondary pest species were collected in the period with an average of 13 387 and 812 individuals per light trap, respectively. Most collected primary pest species were Stenalcidia grosica (Geometridae), Iridopsis subferaria (Geometridae), Eupseudosoma aberrans (Arctiidae) and Psorocampa denticulata (Notodontidae), totalizing for the study period an average of 5 450, 2 162, 2 436 and 1 458 individuals per light trap, respectively. Idalus admirabilis (Arctiidae) was the most collected secondary pest species, averaging 652 individuals/trap. Most primary pest species were collected during the dry season, from April to July, whereas most secondary pest species were collected during the rainy season, from January to March. These differences on seasonal occurrence between the two groups could be due to the fact that many secondary pest species of Eucalyptus in Brazil pupate in the soil, and they need humidity to complete its pupal stage.